Prediction of Anti-SARS CoV-2 Activity from Green Tea Catechin (Camellia sinensis L. Kuntze) Compound Against To Receptors Non-structural Protein 3 (6W6Y) And Non-structural Protein 5 (6M2N) - Roihatul Mutiah; Chamlah Ayatillah; Yen yen Ari Indrawijaya; Arief Suryadinata (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Green tea catechin compounds (Camellia sinensis L. Kuntze) have an antiviral activity such as influenza, hepatitis B, hepatitis C, herpes simplex virus, HIV, and proven in vitro antiviral influenza against NSP5 in SARS CoV. These considerations are used in this study using Non-structural Protein (NSP), namely NSP3 and NSP5 in SARS CoV-2, which have a role in viral replication and transcription. This study aims to predict the physicochemical properties according to the five rules of Lipinski's using swissADME. Prediction of toxicity with LD50 classification using the Protox II online tool. Catechin compound activity based on ligand interaction with NSP3 (PDB ID: 6W6Y) and NSP5 (PDB ID: 6M2N) receptors using Molegro Virtual Docker (MVD) 6.0. The results showed the predictions of physicochemical properties of the (-)-epigallocatechin (EGC), (-)-epicatechin-3-gallate (ECG), and (-)-epicatechin (EC) compounds fulfilled the five rules of Lipinski's. Catechin compounds have toxicity at levels 4 and 6. The activity of catechin compounds on NSP3 (PDB ID: 6W6Y) and NSP5 (PDB ID: 6M2N) receptors indicated that all catechin compounds had inhibitory activity. The best potential activity compound is (-)-epigallocatechin-3-gallate (EGCG) with a rerank score of -102.8200 and -134.1800 Kcal/mol so that EGCG can be recommended as a candidate for the SARS CoV-2 antiviral compound.